Under Neo-colonialism and Othering: West Papuan Case in Bonnie Etherington's The Earth Cries Out - Sukandar, Asael Charis Tewu; Nurcahyani, Eka (Lililacs Journal, 2021)
During 1997-1998, West Papua, the most eastern part of Indonesia, is in the midst of collision between the Indonesian police and the Operasi Papua Merdeka resistance. This study aims to examine the calamity brought by the Neo-colonial power upon the land of West Papua and the forms of Othering done under the Indonesian rule as represented in Bonnie Etherington’s the Earth Cries Out by deploying Kwame Nkrumah’s Neocolonialism to reveal the existing institution that exploits the West Papuan natural resources and Gayatri Spivak’s Othering to unravel the desire of power of the Indonesian government over the West Papuan. The findings show that Neo-colonialism is represented by an international American mining company named freeport, which has become the main beneficiary of the natural resources that lays underneath the West Papuan land, affecting the minor dividens received by Indonesian government and alienate the West Papuan from the richness of their own land. It is also found that the othering process was done by the Indonesian government through the assertion of power presented by Indonesian police stationed in the area, racist remarks by the Indonesian police, job position that favors non-West Papuan people, and a case of sexual harassment towards one West Papuan character in the novel. Moreover, there is an intersecting interest between the American mining company with the Indonesian government in the West Papuan land.